Utilization of MQTT and Radio GPS in Pet Monitoring - Lindawati, Lindawati; Sarjana, Sarjana; Agatha, Adelia (Jurnal Teknologi Informasi dan Pendidikan, 2024)
This research presents an effective and efficient solution for tracking pets using Message Queuing Telemetry Transport (MQTT) based on radio GPS. The study creates a device and application capable of monitoring the whereabouts of pets to prevent their loss by displaying the latitude and longitude of the pet's location. This application provides real-time monitoring and exhibits high accuracy, with minimal differences in latitude and longitude compared to both animal tracking applications and Google Maps. The application's update speed is also impressive, with a delay of only 4.25 seconds. By continuously developing and enhancing this technology, it is expected to provide broader benefits to the pet-loving community.